Aspectos bioecológicos, infraestrutura produtiva e diagnóstico sócio-econômico da pesca de lagosta no estado do Ceará, Brasil - Guimarães, Maria Socorro Sobral (1999)
This thesis monography deals with some bioecological aspects that explain the success of lobster fishing, its productive infraestructure and socio-economic diagnosis of this activity in Ceará State. The main sources of information were the long historical series of data on yield, fishing effort and catch per unit effort, and the gathering of information contained in the literature and direct contact with people involved with fishing, processing and marketing of lobsters. The continental shelf off the northeastern region of Brazil is endowed with outstanding environmental conditions for the calcareous algae substrate to be formed and make up the ideal habitat to tropical spiny lobsters of genus Panulirus over a 83,526 sq. km surface. Ceará State holds 27.6% (23088 sq km) of the total area, 52.3% of the catch, 43.5% (7301355 kg) of the carrying capacity and 42.9% (7.210.644 kg) of the standing stock. Species P. argus and P. laevicauda have 68.9% and 31.1 % of total biomass, the latter being more abundant in areas with depths up to 30 meters whereas the former one is more abundant thereafter. Catchability is 56.6% and optimum fishing intensity and density rates are 5.1 individuals/trap/ha and 1.58 kg/ha. Lobster fishing went through the phases of Development, Acceleration, Stablization and, at the moment, is showing all features of the Depletion Phase, such as downward trend of production, positive growth rates of fishing effort (b = 1,814 and G = 4.1%) and negative growth rates of catch per unit effort (b = 0.0387 and G = - 3.7%). In relation to the optimum values, yield makes up 82.1%, fishing effort, 173.5% and CPUE, 47.3%. Annual yield did not decrease as fast as would be expected, given the current state of overfishing, taken as proven by the CPUE decrease to 52.7% of its maximum sustainable value, namely 0.341 kg per trap/day. As an economic activity, lobster fishing differs from other extractive activities by exploiting common property resources, being hard to forecast yield, trading their products to the external market, being subject to high rates of risks and depreciation, and depending to a high extent on public services. Catching itself concentrates most of capital spending and running costs and its management have assumed the following strategies at different year periods, namely: financial strategy, that maximizes profits (R$ 46.8 million) but no employment (4,120 fishermen), bioeconomic strategy, that maximizes levels off revenues (R$ 76.0 million) and employment (6,606 fishermen), and socioeconomic strategies that maximize job opportunities (10,654 employees at the primary sector) while keeping profits varying about positive and negative values. The current adopted strategy has been the socioeconomic one for whose maintenance reduction in the tax over production transportation and a financial subsidy on fuel consumption. The ideal economic situation should generate R$ 76.0 million in revenues, R$ 42.5 million of profits, 6,606 direct jobs in the primary sector and R$ 3.71 per unit effort, R$ 2.72 of benefit/cost relationship and 55.9% of profit margin. Despite the difficulties, one may conclude that the lobster fishing is still a very important economic activity in Ceará State, being responsible for foreign currency from exportation and a large share of the job opportunities.